Understanding the social implications of higher education - Gonchar N. N., Torgovanova O. N., Shabanova A. E. (Pedagogy, Psychology, Society, 2022)
Higher education used to be considered a waste of time, but now many countries are engaged in improving and promoting this area. An increase in the number of people with higher education leads to both positive and negative effects. These consequences cannot be considered as a whole, since they act both at the macro and micro levels.
Keywords: высшее образование; образование; обучение; общество; иностранный язык; знания; higher education; education; foreign language; society; knowledge; influence